Implementing CSR in the fashion industry: measuring the designers´ perceptions and commitment - Plonka, Magdalena Barbara (2019)
Submitted by Susana Santos (susana.santos@universidadeeuropeia.pt) on 2019-03-25T16:38:10Z No. of bitstreams: 1 Thesis Magdalena Płonka PhD FINAL FILE 21.03.2019.pdf: 3906599 bytes, checksum: 1900ef906cd693558ba1a0daea1c901f (MD5)